2009
DOI: 10.3382/ps.2009-00073
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme complex containing carbohydrases and phytase improves growth performance and bone mineralization of broilers fed reduced nutrient corn-soybean-based diets

Abstract: One experiment was conducted to investigate the benefits of a multi-enzyme complex, containing carbohydrases (from Penicillium funiculosum) and phytase (bacterial 6-phytase) activities, on the performance and bone mineralization of broiler chickens fed corn-soybean meal diets. A total of 2,268 male broilers were allocated to 9 treatments, replicated 6 times, in a randomized complete block design from 1 to 43 d. A positive control (PC) diet formulated to be adequate in nutrients and 4 reduced nutrient diets (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 32 publications
3
38
0
1
Order By: Relevance
“…Birds supplemented with enzymes presented similar tibial calcium weight. Francesch & Geraert (2009) found that reducing dietary nutrient levels resulted in reduced bone ash, calcium, and phosphorus contents in comparison with a standard diet. In addition, those authors observed that supplementing the nutrient-deficient diet with a xylanase, glucanase, and phytase blend, improved the bone mineralization of 21-d-old broilers, promoting similar results as those obtained with a standard diet.…”
Section: Enzyme Supplementation Of Broiler Feeds With Reduced Mineralmentioning
confidence: 98%
“…Birds supplemented with enzymes presented similar tibial calcium weight. Francesch & Geraert (2009) found that reducing dietary nutrient levels resulted in reduced bone ash, calcium, and phosphorus contents in comparison with a standard diet. In addition, those authors observed that supplementing the nutrient-deficient diet with a xylanase, glucanase, and phytase blend, improved the bone mineralization of 21-d-old broilers, promoting similar results as those obtained with a standard diet.…”
Section: Enzyme Supplementation Of Broiler Feeds With Reduced Mineralmentioning
confidence: 98%
“…Results on the use of exogenous enzyme in broiler diets are contradictory. Some researchers undoubtedly point out that the increase in body weight gain is due to the effect of the use of carbohydratases (Mathlouthi et al, 2002;Francesch & Geraert, 2009;Hajati, 2010). Other authors reported an increase in diet digestibility, but not in broiler performance (Marsman et al, 1997;Kocher et al, 2000;Preston et al, 2000), whereas some did not observe any effect (Aftab, 2009).…”
Section: Performance and Some Intestinal Functions Of Broilers Fed DImentioning
confidence: 99%
“…Several alternative methods have been devised over recent years in order to reduce the negative impact of phytate P on the environment and poultry performance. The use of one of these strategies, which includes the administration of microbial phytase, has increased remarkably since the early 1990s and has become a standard practice (Ceylan et al, 2003;Francesch and Geraert, 2009).…”
Section: Introductionmentioning
confidence: 99%